Patients With Rheumatoid Arthritis Increased Risk of Developing Osteoarthritis: A Nationwide Population-Based Cohort Study in Taiwan - Lee, Yung-Heng; Tsou, Hsi-Kai; Kao, Su-Ling; Gau, Shuo-Yan; Bai, Yi-Chiao; Lin, Mei-Chen; Wei, James Cheng-Chung (Frontiers in Medicine, 2020)
Abstract: Objective. To investigate the risk of developing OA in patients diagnosed with RA. Methods. In this study, we presented gender, age, urbanization, occupation and comorbidities in RA cohort and non-RA cohort based on number and percentage. We investigated the OA risk in patients with RA. We conducted a retrospective cohort study with a 13-year longitudinal follow-up in Taiwan. Patients who received RA diagnoses between 2000 and 2012 were enrolled in the study cohort. The Non-RA cohort were 1:1 propensity score matched with the RA cohort by age, gender, index year, urbanization, occupation and comorbidities. The hazard ratios (HRs) and adjusted HRs (aHRs) were estimated after confounders were adjusted. Sensitivity analysis utilizing the Longitudinal Health Insurance Database (LHID) was conducted. Results. We totally enrolled 63626 cases in RA patients (study cohort) and matched controls. In the RA cohort, the crude HR for OA was 2.86 (95% confidence interval (CI), 2.63–3.11, p< 0.001), and the aHR was 2.75(95% CI, 2.52-2.99, p< 0.001). (The study demonstrated that patients with RA had a higher risk for developing OA compared with the non-RA controls. Conclusion. Developing effective OA prevention strategies are necessary in patients with RA. This study finding may be extended to evaluate the risk of OA among other kinds of inflammatory autoimmune diseases. Identifying the key pathogenesis mechanisms are necessary in the future study.